PSYCHOLOGICAL ASPECTS OF PRIVATE PREPARATION OF PRESCHOOL CHILDREN FOR SCHOOL (Conferencea, 2023)
The article provides a theoretical basis for the psychological aspects and importance of moral and voluntary preparation of children of preschool age for school. Features such as independence, organization and discipline in the personal behavior of preschool children are also highlighted.